2013
DOI: 10.4103/0973-6247.106724
|View full text |Cite
|
Sign up to set email alerts
|

Serological investigation for hepatitis E virus infection in the patients with chronic maintenance hemodialysis from southwest of Iran

Abstract: Background and Objectives:A global distribution has been shown for hepatitis E virus (HEV) infection. Although the fecal-oral was considered as the primary infection route, there is controversial evidence for increased risk of the infection and consequent problems in patients on maintenance hemodialysis (HD) with suppressed immunity. The aim is to find if the prevalence of anti-HEV IgG, in patients with maintenance HD is higher than normal population in southwest of Iran.Materials and Methods:During November a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In contrast, cynomolgus monkey I3 (Table 2 ) showed lymphopenia, prolonged viraemia (starting at 39 dpi), and faecal shedding (starting at 19 dpi) without seroconversion until the end of the experiment and possibly beyond that period. Such a pattern of prolonged viraemia and viral elimination without seroconversion or liver enzyme elevation has been described for HEV-infected, immunocompromised individuals [ 42 - 44 ], haemodialysis patients [ 45 ], and an immature neonate [ 44 ]. The protective roles of specific antibodies in controlling HEV infection have been confirmed in non-human primate studies [ 40 , 46 - 48 ] for both naturally acquired and experimentally induced infections [ 38 , 48 , 49 ] and in convalescent human patients [ 50 ].…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, cynomolgus monkey I3 (Table 2 ) showed lymphopenia, prolonged viraemia (starting at 39 dpi), and faecal shedding (starting at 19 dpi) without seroconversion until the end of the experiment and possibly beyond that period. Such a pattern of prolonged viraemia and viral elimination without seroconversion or liver enzyme elevation has been described for HEV-infected, immunocompromised individuals [ 42 - 44 ], haemodialysis patients [ 45 ], and an immature neonate [ 44 ]. The protective roles of specific antibodies in controlling HEV infection have been confirmed in non-human primate studies [ 40 , 46 - 48 ] for both naturally acquired and experimentally induced infections [ 38 , 48 , 49 ] and in convalescent human patients [ 50 ].…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a significant level of the IgG antibody is cleared during the process of hemodialysis. Therefore, using antibody markers to detect HEV infection is accompanied by some shortcomings, especially in HD patients ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning the seroprevalence of HEV infection among HD patients have presented conflicting results. The HEV seropositivity rates reported in HD patients for different countries range as low as 0.9% in France and 2.6% in Italy and as high as 7.3% or more among the adult population in Spain or in Brazil ( 14 ). A case-control study using serology assays conducted in Saudi Arabia reported a prevalence of 4.8% in 83 chronic HD patients vs. 0.3% in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Sylvan et al previously reported no significant difference between HEV antibodies in Swedish HD patients (6%) and control subjects (5.2%) and no IgG anti-HEV seroconversion during chronic HD [38]. An additional report from Iran also did not found statistically significant higher anti-HEV IgG prevalence among patients with chronic HD [39].…”
Section: Discussionmentioning
confidence: 88%